Sensuality Representation Of Guinness Dark Beer Advertising - Migotuwio, Namuri; Ika Indrayati, Refita; Wisnu Wijaya, P.G. (Indonesian Journal of Visual Culture, Design, and Cinema, 2023)
This study examines the rhetorical meaning of "stout" dark beer advertising photos with the Guinness trademark presented with a sensuality approach. Roland Barthes' semiotics is used to reveal symbolic meaning in advertising. In addition, to explain the concept of secrecy and the psychological aspects implied in the advertisement elaborated using Lacan's psychoanalytic theory. Based on an in-depth analysis, it was concluded that the sensuality approach through bodily on Guinness dark beer advertising posters was considered in line with the spirit of the company that wanted to present an elegant, masculine impression and able to accommodate the cultural spirit of patriarchal society in Ireland and the world. In addition, the use of legs and the use of black are considered to be able to represent the history of the slave trade in Ireland and express the discourse of sensuality that developed in the country. Visualization with digital imaging techniques is a bridge to the ideological conflict between sensuality as a concept that is still considered taboo by society and advertising as a medium for commodification of Guinness products.